Terpaan Tren Citayam Fashion Week di Media Sosial dan Pengaruhnya terhadap Persepsi Mahasiswa - Mudrikah, Rika; Mayasari; Oktariani Lubis, Fardiah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The Citayam Fashion Week Trend has become a phenomenon that has attracted a lot of attention from people from various circles. Citayam Fashion Week trens spread quickly on social media, one of which is on social media TikTok. TikTok social media is audio-visual media so that the content presented can be seen and heard and can provide a clear picture of the phenomena that are occurring. This research aims to find out whether there is an influence from exposure to the Citayam Fashion Week trend on TikTok social media on students’ perceptions of fashion. The type of research used is quantitative research with an axplanatory survey method. The sample in this research was 105 students of the FISIP Unsika, class of 2022. This research uses and effect theory. The results obtained in this research are that exposure to Citayam Fashion Week trends on TikTok social media has an influence on students’ perceptions of fashion.